Field and Service Robotics Results of the 9th International Conference - Mejias, Luis; Corke, Peter; Roberts, Jonathan (Springer Tracts in Advanced Robotics,, 2015)
FSR, the International Conference on Field and Service Robotics, is a robotics Symposium which has established over the past ten years the latest research and practical results towards the use of field and service robotics in the community with particular focus on proven technology. The first meeting was held in Canberra, Australia, in 1997. Since then the meeting has been held every two years in the pattern Asia, America, Europe.   Field robots are non-factory robots, typically mobile, that operate in complex, and dynamic environments; on the ground (of earth or planets), under the ground, underwater, in the air or in space. Service robots are those that work closely with humans to help them with their lives. This book present the results of the ninth edition of Field and Service Robotics, FSR13, held in Brisbane, Australia on 9th-11th December 2013. The conference provided a forum for researchers, professionals, and robot manufactures to exchange up-to-date technical knowledge and experience. This book offers a collection of a broad range of topics including: Underwater Robots and Systems, Unmanned Aerial Vehicles technologies and applications, Agriculture, Space, Search and Rescue and Domestic Robotics, Robotic Vision, Mapping and Recognition.